Degradation of Volatile Organic Compounds and Pesticides by Heterogeneous Photocatalysis with Titanium Dioxide - Tuesta, Erika G. (2002)
A new technology for photocatalytic degradation of organic pollutants was investigated. It is based on photocatalytical properties of TiO, nanoparticles, under UV radiation. Four aliphatic alcohols: methanol, ethanol, 2-propanol and 1-butanol, as well as a pesticide: cypermetrhin,where irradiated on nanoparticles of TiO, photocatalist. A cylindrical photoreactor which use a medium pressure Hg lamp, as UV radiation source, was specially designed for this work. Our system was able to follow in situ degradation using a Fourier Transform Infrared Spectrometer (FT-IR) with a gas cell. From infrared spectra obtained a reaction mechanism was proposed. After few minutes of irradiation, complete mineralization were obtained, which indicates that photocatalytic method is an effective technique for degradation to this kind of pollutants.